2003
DOI: 10.1097/01.alc.0000065697.73554.df
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses of Ethanol‐Induced Hyperglycemia

Abstract: These findings indicate important sex differences in the glycemic response to ethanol. In addition, multiple genes likely control this response, independent from genes that are important for the thermic or aversive effects of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Consistent with previous data (Risinger and Cunningham, 1991, 1992; Risinger, 2003), an acute ethanol injection induced a nominal, but non-significant increase in blood glucose levels (see Figure 3B). Blood glucose levels did not increase with repeated ethanol injections, and if anything, were lower in sensitized mice compared with controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous data (Risinger and Cunningham, 1991, 1992; Risinger, 2003), an acute ethanol injection induced a nominal, but non-significant increase in blood glucose levels (see Figure 3B). Blood glucose levels did not increase with repeated ethanol injections, and if anything, were lower in sensitized mice compared with controls.…”
Section: Discussionsupporting
confidence: 93%
“…Acute ethanol administration in normally feeding rodents results in a mild but prolonged hyperglycemia (Oliveira de Souza and Masur, 1981; Souza and Masur, 1982, 1984; Risinger and Cunningham, 1991, 1992; Risinger, 2003), due in part to increased glycogenolysis and decreased glyconeogenesis (see van de Wiel, 2004 for review). Ethanol also acutely inhibits signaling through the insulin receptor (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, one distinction between ErGeN3 and ErGeN10 was the clustered connections of numerous ethanol relevant phenotypes to ErGeN10 . While ErGeN3 correlated with ethanol metabolism rate [67] and blood glucose levels following ethanol treatment [68] , ErGeN10 appears more related to ethanol behavioral phenotypes, including ethanol induced locomotor activation [63] , anxiolysis (Cook et al, unpublished) and sensitization [69] .…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, it is also possible that only testing 29 BXD strains is a limitation of our study. However, other studies have successfully used fewer numbers of strains for QTL analysis and identified significant loci 42‐45 …”
Section: Discussionmentioning
confidence: 99%